Nanotitania Exposure Causes Alterations in Physiological, Nutritional and Stress Responses in Tomato (Solanum lycopersicum) - Tiwari, Manish; Sharma, Nilesh C.; Fleischmann, Paul; Burbage, Jauan; Venkatachalam, Perumal; Sahi, Shivendra V. (Frontiers in Plant Science, 2017)
Titanium dioxide nanoparticles (nanotitania: TiO2NPs) are used in a wide range of consumer products, paints, sunscreens and cosmetics. The increased applications lead to the subsequent release of nanomaterials in environment that could affect the plant productivity. However, few studies have been performed to determine the overall effects of TiO2NPs on edible crops. We treated tomato plants with 0.5, 1, 2 and 4 g/L TiO2NPs in a hydroponic system for two weeks and examined physiological, biochemical and molecular changes.. The dual response was observed on growth and photosynthetic ability of plants depending on TiO2NPs concentrations. Low concentrations (0.5–2 g/L) of TiO2NPs boosted growth by approximately 50% and caused significant increase in photosynthetic parameters such as quantum yield, performance index, and total chlorophyll content as well as induced expression of PSI gene with respect to untreated plants . The high concentration (4g/L) affected these parameters in negative manner. The catalase and peroxidase activities were also elevated in the exposed plants in a dose-dependent manner. Likewise, exposed plants exhibited increased expressions of glutathione synthase and glutathione S-transferase (nearly 3-fold increase in both roots and leaves), indicating a promising role of thiols in detoxification of TiO2NPs in tomato. The elemental analysis of tissues performed at 0.5, 1 and 2 g/L TiO2NPs indicates that TiO2NPs transport significantly affected the distribution of essential elements (P, S, Mg and Fe) in roots and leaves displaying about three fold increases in P and 25% decrease in Fe contents. This study presents the mechanistic basis for the differential responses of titanium nanoparticles in tomato, and calls for a cautious approach for the application of nanomaterials in agriculture.